Mercury Poisoning and Latex Paint - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
Mercury poisoning manifested as acrodynia, reported in a four year old boy in Michigan ten day after the inside of his home was painted with 64 liters of interior latex paint containing phenylmercuric acetate, prompted an investigation by the Division of Environmental Hazards and Health Effects, Centers for Disease Control, Atlanta, GA.